2013
DOI: 10.1016/j.cppeds.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Reunification: The Experiences of Adolescents Living in Transnational Families

Abstract: There are increasing numbers of mothers as well as fathers who engage in long-term migration to support their children and other family members in their home countries. In this article, the current state of the literature about children and adolescents left at home in these transnational families is surveyed and reviewed. The article reviews the effects on children of the process of separation from parents, the impact of gifts and remittances home, communication with distant parents and the quality of life wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 87 publications
(183 reference statements)
1
34
1
Order By: Relevance
“…This figure is consistent with reports in the literature about adolescent adaptation to migration and family reunification (Hernandez, 2013;Schapiro et al, 2013). A recent participatory youth action study found that UIY felt isolated and lacked adult support (Fordham University & VERA Institute, 2015).…”
Section: Behavioral Health Needssupporting
confidence: 81%
See 1 more Smart Citation
“…This figure is consistent with reports in the literature about adolescent adaptation to migration and family reunification (Hernandez, 2013;Schapiro et al, 2013). A recent participatory youth action study found that UIY felt isolated and lacked adult support (Fordham University & VERA Institute, 2015).…”
Section: Behavioral Health Needssupporting
confidence: 81%
“…border for many years, reunifying with parents, seeking better opportunities and fleeing violence in their home countries (Schapiro, Kools, Weiss, & Brindis, 2013;Schapiro, Kools, Weiss, & Brindis, 2015). However, in recent years Guatemala, Honduras and El Salvador, known as the Northern Triangle of Central America, have been plagued with increasing gang and cartel violence, declining governmental and educational infrastructures and increased corruption among law enforcement (Restrepo & Garcia, 2014).…”
Section: Introductionunaccompanied Mexican and Central American Youmentioning
confidence: 99%
“…Both sets of literature mentioned above highlight, directly or indirectly, the centrality of mothers in decisions and realisations concerning child reunification. This situation can in part be linked to the emotional bond between mother and child, whether socially constructed or genetically conditioned (Schapiro et al, ). Qualitative studies have shown that mothers more often than fathers expressed the desire to reunify their children, including when parents within the same couple were interviewed (Barou, ; Hondagneu‐Sotelo, ).…”
Section: Family and Gender Perspectives On Child Migrationmentioning
confidence: 99%
“…The growing share of women acting as pioneer migrants within their families among specific flows (Ambrosini, ; Asis, ) has reignited academic and policy interest in children left‐behind and child migration (Orellana, Thorne, Chee, & Lam, ; Suárez‐Orozco, Todorova, & Louie, ). Stronger emotional bonds between mothers and children compared to those with fathers (Parreñas, ; Schapiro, Kools, Weiss, & Brindis, ), as well as the potentially greater instability of care arrangements for children left‐behind by migrant mothers (Mazzucato & Cebotari, ), suggested these new transnational family arrangements would be temporary and children would be rapidly reunified. However, migrant mothers' more precarious socio‐economic and legal status in the destination countries (Bernhard, Landolt, & Goldring, ; Bonizzoni, ), as well as more complex family situations (Caarls, Haagsman, Kraus & Mazzucato, ), emerged as serious impediments to reunifying their children, particularly through the legal family reunification procedure.…”
Section: Introductionmentioning
confidence: 99%
“…After such a long separation, the reunification of children with their parents in their receiving countries is a complicated process that has been the subject of several studies (e.g. Bonizzoni 2012;Schapiro et al 2013;Suárez-Orozco and Suárez-Orozco 2001). These works have underlined the emotional difficulties inherent to family reunion, but also the malleability of interpersonal relationships and the resilience of migrants' children.…”
Section: Introductionmentioning
confidence: 98%